Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Sorting Solutions of Equations

Sort each equation according to whether it has one solution, infinitely many solutions, or no solution.

[tex]\[ 5(x-2)=5x-7 \][/tex]
[tex]\[ -3(x-4)=-3x+12 \][/tex]
[tex]\[ 4(x+1)=3x+4 \][/tex]
[tex]\[ -2(x-3)=2x-6 \][/tex]
[tex]\[ 6(x+5)=6x+11 \][/tex]

A. One Solution
B. Infinitely Many Solutions
C. No Solution


Sagot :

Certainly! Let's go through each of the given equations step-by-step to determine the solution type: one solution, infinitely many solutions, or no solution.

### 1. Equation: \( 5(x-2) = 5x - 7 \)

Let's expand and simplify both sides:
[tex]\[ 5(x - 2) = 5x - 10 \][/tex]

The equation now is:
[tex]\[ 5x - 10 = 5x - 7 \][/tex]

Subtract \( 5x \) from both sides:
[tex]\[ -10 = -7 \][/tex]

This is a contradiction. Therefore, this equation has No Solution.

### 2. Equation: \( -3(x-4) = -3x + 12 \)

Let's expand and simplify both sides:
[tex]\[ -3(x - 4) = -3x + 12 \][/tex]
[tex]\[ -3x + 12 = -3x + 12 \][/tex]

Both sides are identical. Therefore, this equation has Infinitely Many Solutions.

### 3. Equation: \( 4(x+1) = 3x + 4 \)

Let's expand and simplify both sides:
[tex]\[ 4(x + 1) = 4x + 4 \][/tex]

Now, the equation is:
[tex]\[ 4x + 4 = 3x + 4 \][/tex]

Subtract \( 3x \) from both sides:
[tex]\[ x + 4 = 4 \][/tex]

Subtract 4 from both sides:
[tex]\[ x = 0 \][/tex]

So, this equation has One Solution.

### 4. Equation: \( -2(x-3) = 2x - 6 \)

Let's expand and simplify both sides:
[tex]\[ -2(x - 3) = -2x + 6 \][/tex]

The equation now is:
[tex]\[ -2x + 6 = 2x - 6 \][/tex]

Add \( 2x \) to both sides:
[tex]\[ 6 = 4x - 6 \][/tex]

Add 6 to both sides:
[tex]\[ 12 = 4x \][/tex]

Divide by 4:
[tex]\[ x = 3 \][/tex]

So, this equation has One Solution.

### 5. Equation: \( 6(x+5) = 6x + 11 \)

Let's expand and simplify both sides:
[tex]\[ 6(x + 5) = 6x + 30 \][/tex]

The equation now is:
[tex]\[ 6x + 30 = 6x + 11 \][/tex]

Subtract \( 6x \) from both sides:
[tex]\[ 30 = 11 \][/tex]

This is a contradiction. Therefore, this equation has No Solution.

### Summary

Let's sort the equations based on their solutions:

- Infinitely Many Solutions:
- \( -3(x-4) = -3x + 12 \)

- No Solution:
- \( 5(x-2) = 5x - 7 \)
- \( 6(x+5) = 6x + 11 \)

- One Solution:
- \( 4(x+1) = 3x + 4 \)
- [tex]\( -2(x-3) = 2x - 6 \)[/tex]